Ultrasound image guidance and robot impedance control for beating-heart surgery. (December 2018) - Cheng, Lingbo; Tavakoli, Mahdi
Abstract: A novel control method is proposed for master–slave telerobotic beating-heart surgery to solve the challenges of rapid heart motion and oscillatory haptic feedback. In this paper, the ultrasound imaging-based control algorithms are used to make the slave robot compensate for the heart motion automatically. Issues including slow sampling rate and time delay caused by ultrasound imaging are addressed by a cubic interpolation and an extended Kalman filter (EKF), respectively. Meanwhile, to provide the human operator (surgeon) a feeling of operating on an idle heart, an impedance model is designed for the master robot. The proposed method is validated through experiments.